Energy Harvesting and Storage: Energy Harvesting and Storage with Soft and Stretchable Materials (Adv. Mater. 19/2021). Issue 19 (11th May 2021) - Vallem, Veenasri; Sargolzaeiaval, Yasaman; Ozturk, Mehmet; Lai, Ying‐Chih; Dickey, Michael D.
Abstract : In article number 2004832, Michael D. Dickey and co‐workers highlight methods to convert ambient sources of energy into electricity using soft and stretchable materials. The ability to harness energy from the environment allows soft and stretchable devices to be tetherless, thereby leading to greater range of motion for soft robots, better mechanical compliance for wearables and e‐skins, and increased applications for electronics.